Pathology of pulmonary tuberculosis: has the tiger changed it’s stripes? - Heena Maulek Desai; Pradeep Vaideeswar; Manish Gaikwad; Gayathri Prashant Amonkar (Autopsy and Case Reports, 2022)
Background: India accounts for the highest number of TB cases globally (almost one-fifth of the global burden and almost two-thirds of the cases in South East Asia. Furthermore, the development of drug resistance of varying levels such as multi-drug resistant TB (MDR-TB), extensively-drug resistance TB (XDR-TB) and total-drug resistant TB (TDR-TB) has been on the increase, and now India also features in the 27 high-MDRTB-burden countries. Almost parallel to these developments, in the last few years, we have been encountering less common morphological forms of pulmonary TB (PTB) at autopsies. With these less common manifestations of the disease, we undertook this study to examine the changing trends in the morphological pattern of pulmonary TB over the recent years.